Invertebrate stress responses as molecular biomarkers in ecotoxicology - Guven, Kemal (1994)
All organisms studied so far respond to heat shock by inducing the synthesis of a number of proteins called heat shock proteins(LISPs). This universal response can also be induced by a variety of stressors, including heavy metal ions and organic and organo-metallic compounds. As a result, the stress response has recently attracted the attention of ecotoxicologists for use in environmental biomonitoring. In the present study, we have investigated the stress responses of two different organisms ; namely the free-living soil nematode Caenorhiabdities elegans(both wild-type and transgenic strains) and the freshwater crustacea Asellus aquazicus. We have also explored the possible use of these model systems in environmental monitoring using different techniques which include metabolic labelling with subsequent one-dimensional electrophoresis and autoradiography, and one- or two-dimensional western blotting using antibodies specific to stress protein 70. The study with A. aquaticus shows that this organism exhibits a classical stress response. The exposure of asellids to heat shock-treatment (26°C ; 13°C above the standard maintenance temperature) or to sublethal concentrations of metal ions (Cd++ and Cu++) resulted in the induction of at least 5 putative HSPs which belong to several major HSP families (HSP100, HSP90 and possibly HSP60). An increase in the synthesis of smaller sizes of polypeptides (25-35 kD) should be also noted. Moreover, the time-course of heat versus heavy metal stress-response in this organism suggests that the pattern of stress-protein synthesis changes considerably with increasing exposure time ; notably the response to heat is more transient than that to heavy metals. However, HSP70 does not appear to be the major stress protein induced in this organism. The presence of low molecular weight (LMW) proteins which react with anti-HSP70 antibodies and the apparent deficiency of classical 70 kD stress proteins in A. aquaticus, both suggest that HSP70s in this organism are for some reason prone to degradation. In the nematode C .elegans, shifting the culture temperature from 20°C to 34°C induces the synthesis of a set of HSPs corresponding to the HSP90, HSP70 and small HSP families. There are at least nine members of the hsp7O multigene family in C. elegans ; some members are expressed constitutively while others are stress inducible. W e have studied the effects of heat and heavy metal (cadmium) stress on the expression patterns of the HSP70 protein family in the nematodes by one- and two-dimensional Western blotting using a monoclonal anti-HSP70 antibody that recognises a conserved epitope shared by most HSP70 family members. Constitutive C. elegans HSP70s (expressed at 20°C) are almost undetectable on one-dimensional immunoblots, but chemiluminescent probing of two-dimensional blots reveals a complex pattern of several HSP70s pots .Mild heats hock at 31° C induces a doublet HSP70 band on one-dimensional blots, of which the heavier component (75 kD) is more prominent than the lighter (73 kD). On two-dimensional blots, this pattern is shown to be more complex with a prominent 75 kD spot newly induced and several other spots intensified. Severe heat shock at 34°C strongly induces both 75 and 73 kD bands on one-dimensional blots; two dimensional analysis reveals a series of novel and/or elevated 73 and 75 kD spots. Treatment with cadmium( 16 ppm) at 31° C gives a different pattern of spots as compared with 31 °C alone ; several spots show enhanced while some are newly expressed, and not all of these are present at 34°C. These results indicate that related members of the HSP70 protein family in C. elegans are independently regulated in response to different forms of stress. The possible significance of these findings is discussed in relation to the possible use of stress responses s environmental biomonitors. We have also utilised a stress-inducible C. elegans strain (CB4027) for monitoring environmental contamination. This transgenic strain carries integrated copies of the Drosophila hsp70 promoter fused to an E.coli lacZ reporter gene. When exposed to heat shock or to several environmentally relevant stressors, the transgenic strain expresses the reporter product, 3-galactosidase, which can easily be quantified or localised in situ in stained worms or on Western blots (apparently enzymatically active as a 170 kD form). We have exposed transgenic worms to a variety of toxicants at an elevated temperature (32°C) just below that required for heat shock (34°C), in order to obtain optimal transgene induction. Exposure of nematodes to several heavy metals (e. g. Cd+, Hg++, Zn+, Sn++, Mn++ and Ag+), organometallic toxicants (tributyltin) or organic pollutants (lindane) induces ß-galactosidase expression in a dose-dependent manner. Cadmium is found to be by far the strongest inducer of transgene activity amongst the agents tested, although tributyltin is an effective inducer at ppb levels. The effects of mixtures of divalent metal ions (Cd++/Ca++, Cd++/Zn++ and Cd++/Hg++) on ß-galactosidase expression have been also investigated. All three divalent ions tested in combination with cadmium significantly inhibit cadmium-induced transgene activity in comparison to cadmium alone. In the case of Cd++/C++ mixtures, a marked inhibition of Cd++ accumulation by worm tissues has also been demonstrated, directly related to the Ca++ concentration. These effects may represent competition for metal-ion uptake through calcium channels. Our results show that this transgenic system works well within strictly defined assay conditions, and can detect clear responses over a 7h exposure period to environmentally relevant toxicants at sublethal concentrations well below the 24 or 48h LCSO values. However, there is a need for careful characterisation and containment of any transgenic organism if it is to be used as environmental monitoring tool.